Preservation of the artistic heritage of Ukrainian Sich Riflemen: problems and prospects - Рожак-Литвиненко, Ксенія Богданівна (Theory and practice of design, 2019)
The condition and the problems of preservation the artistic heritage of USS are discussed in the dynamics of the development from the creation of LUSS to the present day. There is investigated that the creation of the USS collection began in 1915 by the efforts of «Boyova uprava» (Military Council) of USS in Vienna. Most of this collection was transferred in 1917 to the National museum in Lviv; a large collection of works by USS from 1925 remained in the military monuments’ department at the Museum of Shevchenko Scientific Society, and from 1939 ‑ scattered on funds the Museum of Liberation Struggle in Prague and Lviv historical museum. In August, 1952 under the special instructions of the Committee for cultural and educational institutions under the Council of Ministers of the USSR in the boiler room of LNNB were burned around 2,300 exhibits from special funds of Lviv museums, which included all USS paintings and works on the history of Ukrainian Riflers. There are revealed the facts of finding more than 800 pieces of USS graphics in the special funds of Slavic Library in Prague (1998) as well as single works of artists of the USS in the National Museum in Krakow, the Lviv History Museum and in private collections in Ukraine and abroad. It is concluded that the number of surviving works doesn’t give the complete picture of the scope and nature of the USS artistic groupment’s activity.